Hospital‐wide implementation of an electronic‐workflow solution aiming to make surgical practice improvement easy. Issue 3 (21st October 2016) - Sakowska, Magdalena M.; Thomas, Megan V.; Connor, Saxon; Roberts, Ross
Abstract : Background: In measuring quality of health‐care delivery, digital infrastructure is essential. The aim at this tertiary centre was to create a hospital‐wide workflow system that collected data prospectively as part of daily practice. Methods: In moving towards an electronic health record, a hospital‐wide integrated workflow system was introduced in 2013, which electronically managed the perioperative patient journey while simultaneously facilitating surgical audit. Analysis of its implementation was carried out presenting early outcomes using general surgery as an example. Results: Theatre‐bookings (44 953) were made with compliance approaching 90% for all services. Of 7179 general surgical operations over 24 months, 5785 (80%) had an operation note created using the new system. Cumulative summation of uptake of synoptic operative reporting (SOR) for laparoscopic cholecystectomy (LC) was 81% with documentation being superior in terms of antibiotic use and steps to safe cholecystectomy ( P  < 0.001). A LC SOR took 4 min to complete (interquartile ranges 2–5 min, n  = 425) and was immediately available on the day of surgery compared to narrative operative reports taking 2 days (interquartile ranges 1–5 days, n  = 174) ( P  < 0.001). From July 2014 to November 2015, 557 (10%) complications were recorded for 5749 general surgical operations with 99% of complications being reviewed. Conclusion: The rapid and sustained uptake of both theatre‐bookings and SOR likely reflect high end‐user satisfaction with the system. Service metrics indicate a significant improvement in the time of delivery. The ability to seamlessly complete the audit cycle at an individual, department and hospital level has been achieved.